Visible‐Light Photocatalytic Intramolecular Cyclopropane Ring Expansion. Issue 27 (6th June 2017) - Luis‐Barrera, Javier; Laina‐Martín, Víctor; Rigotti, Thomas; Peccati, Francesca; Solans‐Monfort, Xavier; Sodupe, Mariona; Mas‐Ballesté, Rubén; Liras, Marta; Alemán, José
Abstract: Described herein is a new visible‐light photocatalytic strategy for the synthesis of enantioenriched dihydrofurans and cyclopentenes by an intramolecular nitro cyclopropane ring expansion reaction. Mechanistic studies and DFT calculations are used to elucidate the key factors in this new ring expansion reaction, and the need for the nitro group on the cyclopropane. Abstract : Expansion project : A new visible‐light photocatalytic strategy for the synthesis of enantioenriched dihydrofurans and cyclopentenes through a ring expansion process is presented. Mechanistic and computational studies rationalize the key factors of the reaction.